Optimalisasi Fungsi dan Potensi Masjid: Model Pemberdayaan Ekonomi Masyarakat Berbasis Masjid di Kota Tasikmalaya - Asep Suryanto; Asep Saepulloh (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2016)
The purpose of this study are 1) to identify the economic potential possessed a mosque in the city of Tasikmalaya, 2) to identify the activities performed mosque in the city of Tasikmalaya, 3) to analyze the economic potential of the community around the mosque, especially worshipers of the mosque in the city of Tasikmalaya, 4) to formulate a model of mosque economic empowerment in the city of Tasikmalaya. This research is a qualitative study using grouded research methods that is advanced from the empirical toward the conceptual-theoretical level. The technique of collecting data using interviews, observation, and questionnaries. The results of research showed the following: 1) The economic potential possessed jami mosque in the city of Tasikmalaya includes potential funding of mosques each month between Rp. 400.000, - s / d Rp. 1.000.000, - on 56% jami mosque, while 44% are above Rp. 1.000.000, -. Type the mosque fund in the form of funds for donations, donation, charity malls, and endowments. As for the source of the donations of individuals, governments, businesses themselves DKM, and donations from organizations and companies. There is a mosque whose own treasury in the form of still modest. 2) the potential activities of the mosque as the carrying capacity of the economic empowerment of the mosque is the majlis taklim form study groups of mothers, fathers, and adolescents and the youth of the mosque. Some 86% of respondents agreed that the mosque functioned as a place of economic empowerment. 3) The economic potential of the mosque's congregation are categorized into two groups, namely muzaki and mustahik, with the percentage of 50:50. 4) Design of the mosque economic empowerment model that can be formulated based on the potential of the mosque provided is integrated model between agencies ZIS, Islamic microfinance and economic empowerment.